Characters of female commercial sex workers in the Tegal Panas region - Cholifah, Nur; Iin Purnamasari; Pipit Mugi Handayani (Universitas Islam Malang, 2022)
Becoming a Commercial Sex Worker is a disaster because this profession is a disgrace to practitioners, their families, and society. This study aims to describe the character of commercial sex workers who work in Tegal Panas. This study uses qualitative research with in-depth interview data collection techniques, observation, and documentation. This study uses data sources in the form of primary data and secondary data. Informants in this study were 11 sex workers in the Tegal Panas area who were randomly selected. The analysis technique used is source triangulation and technique triangulation. Researchers use an interactive model whose elements include data collection, data condensation, data presentation, and conclusion. The results of the study show that commercial sex workers in the Tegal Panas area have a pragmatic character to earn money easily without having to work hard. Tegal Panas Commercial Sex Workers have the character of not caring about the spread of sexually transmitted diseases to themselves and others. She has a character that violates decency because she seduces a man who is not her husband, dresses sexy, and dresses excessively. The character of Commercial Sex Workers is confused because on the one hand there is a desire to return to the right path someday, but for now, they are still comfortable living life as Commercial Sex Workers.